2003
DOI: 10.1029/2003gb002035
|View full text |Cite
|
Sign up to set email alerts
|

Modeling temporal and large‐scale spatial variability of soil respiration from soil water availability, temperature and vegetation productivity indices

Abstract: [1] Field-chamber measurements of soil respiration from 17 different forest and shrubland sites in Europe and North America were summarized and analyzed with the goal to develop a model describing seasonal, interannual and spatial variability of soil respiration as affected by water availability, temperature, and site properties. The analysis was performed at a daily and at a monthly time step. With the daily time step, the relative soil water content in the upper soil layer expressed as a fraction of field ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
504
9
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(569 citation statements)
references
References 64 publications
42
504
9
7
Order By: Relevance
“…[59] Reichstein et al [2003] used an elaborate model inversion approach in which Vc max -m and LAI-m were independently fitted to Fc and LE relationships. Using a single response variable to fit two parameters, they averaged the best fit parameter combination for Fc and LE to infer the pair of either Vc max -m or LAI-m relationships that best fit the two fluxes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[59] Reichstein et al [2003] used an elaborate model inversion approach in which Vc max -m and LAI-m were independently fitted to Fc and LE relationships. Using a single response variable to fit two parameters, they averaged the best fit parameter combination for Fc and LE to infer the pair of either Vc max -m or LAI-m relationships that best fit the two fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Some model inversion approaches have been used previously to extract ecosystem parameters from flux measurements [Reichstein et al, 2003]. However, these previous approaches implicitly fix (or do not include) one or more of the three critical canopy parameters (LAI, Vc max , and m) and do not constrain the solution of the unmeasured parameters using both CO 2 and energy fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…4). Several studies indicate a link between soil respiration and plant activity through the phenological control on root respiration fluxes (Hö gberg et al, 2001;Janssens et al, 2001;Reichstein et al, 2003;Curiel et al, 2004). For this forest, a correlation between root growth and leaf area expansion was observed by Joslin et al (2001), with the highest root elongation intensity taking place after the completion of leaf area expansion.…”
Section: Root Respiration Sourcesmentioning
confidence: 99%
“…Numerous studies have shown that decomposition rates are lower during drier soil conditions independent of a change in temperature (e.g. Reichstein et al 2003;Borken et al 2006). Soil moisture may, however, aVect microbial activity negatively both during dry conditions by limiting the availability of water, and during wet conditions by limiting diVusion of O 2 through the soil.…”
Section: Introductionmentioning
confidence: 99%